Shared decision-making about birth after cesarean: review study - Seyede Zahra Hoseini Haji; Mahboobeh Firoozi (Mashhad University of Medical Sciences, 2020)
Introduction: Although vaginal birth after cesarean is a more appropriate alternative comparing to repeat cesarean for eligible individuals, making decision between these two choices is a challenging process and depends on the decision of care providers and mothers. The studies about shared decision making showed different results about mode of birth after cesarean; therefore, this study was performed with aim to review shared decision making about knowledge, decisional conflict and choosing mode of delivery after cesarean. Methods: In this study, for access to the related articles, search was done on PubMed, Scopus, up to date, google scholar, Cochrane and web of science using the MESH-related keywords including "Vaginal birth after cesarean", "Shared decision making", "decision Aid" and "Counseling", as well as Persian databases off SID, magiran and IranMed from October 2018 to July 2019. The quality of the articles was assessed using the Consort Checklist 2017. Results: From the total of 120 articles found in the databases, 4 articles entered the study according to inclusion criteria. In various studies, Shared decision making methods had a contradictory effect on choosing vaginal birth after cesarean, but had a significant effect on knowledge and decisional conflict. Conclusion: The use of Shared decision making methods increases the knowledge of women with previous cesarean about choosing the mode of delivery and decreases the decisional conflict. Since the results about choosing birth after cesarean are inconsistent, further studies are needed.